Notch3 and DeltaB maintain Müller glia quiescence and act as negative regulators of regeneration in the light‐damaged zebrafish retina. Issue 3 (23rd September 2020) - Campbell, Leah J.; Hobgood, Joshua S.; Jia, Meng; Boyd, Patrick; Hipp, Rebecca I.; Hyde, David R.
Abstract: Damage to the zebrafish retina stimulates resident Müller glia to reprogram, reenter the cell cycle, divide asymmetrically, and produce neuronal progenitor cells that amplify and differentiate into the lost neurons. The transition from quiescent to proliferative Müller glia involves both positive and negative regulators. We previously demonstrated that the Notch signaling pathway represses retinal regeneration by maintaining Müller glia quiescence in zebrafish. Here we examine which Notch receptor is necessary to maintain quiescence. Quantitative RT‐PCR and RNA‐Seq analyses reveal that notch3 is expressed in the undamaged retina and is downregulated in response to light damage. Additionally, Notch3 protein is expressed in quiescent Müller glia of the undamaged retina, is downregulated as Müller glia proliferate, and is reestablished in the Müller glia. Knockdown of Notch3 is sufficient to induce Müller glia proliferation in undamaged retinas and enhances proliferation during light damage. Alternatively, knockdown of Notch1a, Notch1b, or Notch2 decreases the number of proliferating cells during light damage, suggesting that Notch signaling is also required for proliferation during retinal regeneration. We also knockdown the zebrafish Delta and Delta‐like proteins, ligands for the Notch receptors, and find that the deltaB morphant possesses an increased number of proliferating cells in the light‐damaged retina. As with Notch3, knockdown of DeltaB is sufficient to induce Müller glia proliferation in the absence of light damage. Taken together, the negative regulation of Müller glia proliferation in zebrafish retinal regeneration is mediated by Notch3 and DeltaB. Main Points: Notch3, expressed in Müller glia, and DeltaB, expressed in neurons, mediate Müller glia quiescence in the undamaged zebrafish retina. Notch3 and DeltaB negatively regulate Müller glia and NPC proliferation during zebrafish retinal regeneration.